Retinoid X Receptors Intersect the Molecular Clockwork in the Regulation of Liver Metabolism - De Cosmo, Salvatore; Mazzoccoli, Gianluigi (Frontiers in Endocrinology, 2017)
Liver metabolic pathways are driven by the biological clock and appropriate timing of 24-hour patterns of metabolic gene expression as well as anabolic/catabolic processes with wake related activity/feeding and sleep related resting/fasting cycles preserves hepatic healthiness. The interplay among the liver metabolic pathways and the molecular clockwork is geared by the nuclear receptors, ligand-dependent transcription factors that gauge the cellular nutritional status and redox balance, bind hormones and metabolites and modulate the transcription of thousands target genes through their DNA-binding domain. Several nuclear receptors in the liver oscillate with circadian rhythmicity and among these the retinoid X receptors play a key role in metabolism regulation intersecting with the cogs of the molecular clockwork.